2013
DOI: 10.1089/fpd.2012.1386
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Enteric Pathogens During Butterhead Lettuce Growth: Crop Stage, Leaf Age, and Irrigation

Abstract: The survival of Salmonella enterica serovar Thompson and Escherichia coli O157 was investigated on growing butterhead lettuce plants in the plant-growth chamber and greenhouse. All inoculation tests were made under conditions that approximate the greenhouse conditions for butterhead lettuce cultivation in Flanders (Belgium). The survival and proliferation of the pathogens on the leaves was determined at days 0, 4, and 8 after inoculation using standard plating techniques on selective medium. In the growth cham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 25 publications
2
35
0
Order By: Relevance
“…As the initial inoculum level was higher than the maximum carrying capacity of the lettuce leaves, which is around 6 log CFU/g [61,62], the pathogen load on the leaves indeed declined. It has, however, already been shown that E. coli O157 is able to grow in the lettuce phyllosphere under high humidity conditions [61,63].…”
Section: Limitations Of the Datamentioning
confidence: 99%
See 1 more Smart Citation
“…As the initial inoculum level was higher than the maximum carrying capacity of the lettuce leaves, which is around 6 log CFU/g [61,62], the pathogen load on the leaves indeed declined. It has, however, already been shown that E. coli O157 is able to grow in the lettuce phyllosphere under high humidity conditions [61,63].…”
Section: Limitations Of the Datamentioning
confidence: 99%
“…As the initial inoculum level was higher than the maximum carrying capacity of the lettuce leaves, which is around 6 log CFU/g [61,62], the pathogen load on the leaves indeed declined. It has, however, already been shown that E. coli O157 is able to grow in the lettuce phyllosphere under high humidity conditions [61,63]. Furthermore, we remark that the high inoculum density could also bias other aspects of E. coli O157 fitness in the phyllosphere, among which are the transition to a viable but non-culturable state [52] or changes in capacity to attach [64,65].…”
Section: Limitations Of the Datamentioning
confidence: 99%
“…However, (Brandl and Amundson, 2008), reported higher population of Salmonella enterica on young leaves than on middle leaves harvested from mature romaine lettuce heads, suggesting that leaf age may affect pre-harvest as well as on farm post-harvest colonization. The moist conditions between the folded inner leaves may contribute to the survival of enteric pathogens in the lettuce head (Van der Linden et al, 2013a).…”
Section: Factors Linked To the Adherence Survival And Internalisatiomentioning
confidence: 99%
“…They found that higher numbers of endogenous microorganisms on lettuce leaves reduced S. Enteritidis adhesion. Some experimental studies have reported that survival of Salmonella in lettuce during growing is relatively short (4-8 days) (Van der Linden et al, 2013a). However, it also has been reported that Salmonella persisted for up to 63 days and 231 days on lettuce and parsley, respectively (Islam et al, 2004b).…”
Section: Factors Linked To the Adherence Survival And Internalisatiomentioning
confidence: 99%
“…[1][2][3][4][5] Particularly, irrigation water was implicated in several reported outbreaks linked to consumption of contaminated vegetables. One such case was related with an outbreak of Escherichia coli O157:H7 in Central Valley, California, from the consumption of contaminated lettuce and with a Salmonella Saintpaul outbreak in Mexico likely associated with contaminated Serrano peppers.…”
Section: Introductionmentioning
confidence: 99%